Critical Analysis of Cases Violation Ethics and Public Accountant Standards in Indonesia - Yuliana Resca; Yanuar Ramadhan (Universitas Islam Lamongan, 2022)
Accountants who provide services to the public must gain the trust of the public. The purpose of this study is to analyze cases of violations, the impact of violations, the code of ethics of public accountants that have been violated, the best solutions for public accountants in the future. The research method used is literature study. The occurrence of violations such as collusion between accountants and clients, not maintaining integrity, competence, independence, morals or facts. In conclusion, violations committed by KAP can cause losses to investors, lose public trust in public accountants, and harm the accountants themselves. This study places more emphasis on the code of ethics that was violated in the KAP case and future solutions for the KAP